The Agenda 2030 as an Instrument to Configure a Global Citizenship from a Human Right Approach: Challenges and Strategies (Comillas Journal of International Relations, 2020)
Since the end of the last decade of the 20th century, the international system has undergone transformation in a more intense and visible way than in other periods as a result of globalization. The relations of political and economic power between States have changed, but even more significant is the emergence and influence of non-state actors on international dynamics and structures, transcending the traditional statocentric paradigm. This article aims to analyze the concept of “global citizenship” as a process of empowerment of a civil society that is increasingly aware of the problems that affect their lives at the local and global level, its link with human rights regimen and the role that the 2030 Agenda represents to advance in its constitution and capacity to influence the achievement of sustainable development.
Keywords: 2030 Agenda; human rights; global citizenship